Trade credit and pricing: An empirical evaluation - Niklas Amberg; Tor Jacobson; Erik von Schedvin (Sveriges Riksbank, 2018)
We empirically investigate the proposition that firms charge premia on cash prices in transactions involving trade credit. Using a comprehensive Swedish panel dataset on product-level transaction prices and firm-characteristics, we relate trade credit issuance to price setting. In a recession characterized by tightened credit conditions, we find that prices increase significantly more on products sold by firms issuing more trade credit, reflecting their larger exposures to increased funding costs and counterparty risks. Our results thus demonstrate the importance of trade credit for price setting and show that trade credit issuance induces a channel through which financial frictions affect prices.
Keywords: E31; E32; D22; G30; L11; 330; Trade credit; prices; inflation; liquidity; counterparty risk